ANALISIS KINERJA PEGAWAI PADA DINAS TENAGA KERJA, KEPENDUDUKAN DAN TRANSMIGRASI KABUPATEN GOWA - Andi Widiawati; Karno. B Karno. B (AkMen JURNAL ILMIAH, 2008)
Analyzed of Performance by Employee on Employment, Population and Transmigration Instance Gowa regency. These research aimed : (1) To know what affected of compensation variable toward performance by employee, (2) To know what affected of facility variable toward performance by employee, (3) To know what affected of job environment variable toward performance by employee, (4) To know what affected of education variabel toward performance by employee, (5) To know what affected of facility variable toward skill by employee, (6) To know what affected of education variabel toward skill by employee, (7). To know what affected of skill variable toward performance by employee. These research applied On Employment, Population and Transmigration Instance Gowa Regency, with total population as amount 51 employee. The method of take sample applied based on sensus method with take in all of population as amount 51 employees. In these research used of data analyse as follows : (1) descriptive statistic analyzed, (2) Path analyzed. These research to teste : (1) What compensation variable (x1), facility (x2), job environment (x3), education (x4) and skill (y1) to affected in positive and significant toward performance variable ( y2), ( 2). What the compensation ( x1), facility ( x2), job environment ( x3) and Education ( x4) affected in positive and significant toward skill (y1). The result obtained : (1) Compensation variable (x1), facility (x2), Job environment (x3), education (x4) and Skill (y1) affected in positive and significant toward performance (y2). (2) facility variable (x2) and education variable (x4) affected positive and significant toward skill variable ( y1).